2012
DOI: 10.1152/ajpregu.00196.2011
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal modulation of the heat shock response: insights from fish with divergent cortisol stress responses

Abstract: LeBlanc S, Höglund E, Gilmour KM, Currie S. Hormonal modulation of the heat shock response: insights from fish with divergent cortisol stress responses. Am J Physiol Regul Integr Comp Physiol 302: R184-R192, 2012. First published October 26, 2011 doi:10.1152/ajpregu.00196.2011.-Acute temperature stress in animals results in increases in heat shock proteins (HSPs) and stress hormones. There is evidence that stress hormones influence the magnitude of the heat shock response; however, their role is equivocal. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 58 publications
(74 reference statements)
4
29
0
Order By: Relevance
“…For example, increased expression of HSC 70 is thought to be related to high temperature tolerance in killifish (Fangue et al, 2006). Instead, our results are consistent with those of a recent study of LeBlanc et al (LeBlanc et al, 2012), who found that rainbow trout with a low cortisol response to stress did not increase HSP/HSC expression after heat stress as much as fish with a high cortisol response and, even though there was significant difference in HPS/HSC levels, CT max values were similar. Perhaps in salmonids, the resting HSP 90β and HSC 70 levels are not as important in defining CT max per se as other cellular and physiological traits.…”
Section: Discussionsupporting
confidence: 91%
“…For example, increased expression of HSC 70 is thought to be related to high temperature tolerance in killifish (Fangue et al, 2006). Instead, our results are consistent with those of a recent study of LeBlanc et al (LeBlanc et al, 2012), who found that rainbow trout with a low cortisol response to stress did not increase HSP/HSC expression after heat stress as much as fish with a high cortisol response and, even though there was significant difference in HPS/HSC levels, CT max values were similar. Perhaps in salmonids, the resting HSP 90β and HSC 70 levels are not as important in defining CT max per se as other cellular and physiological traits.…”
Section: Discussionsupporting
confidence: 91%
“…Reconstituted DNase (8 µL; 15,000 U/mL) was added to each aliquot of saline-diluted RBCs along with protease inhibitor cocktail (0.98 mM; Sigma Aldrich). Soluble protein from RBCs was then extracted as in LeBlanc et al (2011). Both tissue and RBC protein concentrations were determined using the Bio-Rad DC Protein Assay for microtitre plates.…”
Section: Protein Extractions and Hsp70 Immunoblottingmentioning
confidence: 99%
“…Protein extraction and Western blotting were performed to detect and quantify HSP70 in liver, blubber, and plasma as in LeBlanc et al (2012). Lung tissue from the same animals was also examined (data not shown).…”
Section: Western Blottingmentioning
confidence: 99%